2011
DOI: 10.1080/1357650x.2010.513385
|View full text |Cite
|
Sign up to set email alerts
|

Strength of lateralisation for processing facial emotion in relation to autistic traits in individuals without autism

Abstract: A great number of studies have shown that non-clinical individuals rely predominantly on the right hemisphere to process facial emotion. Previous studies have shown that males suffering from Asperger's syndrome show a typical right hemisphere bias for processing facial emotion (happiness and sadness) but a reduced right hemisphere bias for processing facial identity. This study looks at the lateralisation of all six basic emotions using the chimeric faces test in 64 non-clinical participants (32 males, 32 fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 43 publications
1
18
1
Order By: Relevance
“…This is in line with findings that basic emotion identification is intact, but more complex tasks produce recognition errors in ASD (Castelli, 2005). Interestingly, one study (Vladeanu et al, 2012) reported that the discrimination of fear was lateralized to the right hemisphere in patients with ASD, which in this case might have interfered with the damage of the right amygdala. Gainotti (2012) proposed that the right amygdala is primarily responsible for automatic emotion processing.…”
Section: Discussionsupporting
confidence: 85%
“…This is in line with findings that basic emotion identification is intact, but more complex tasks produce recognition errors in ASD (Castelli, 2005). Interestingly, one study (Vladeanu et al, 2012) reported that the discrimination of fear was lateralized to the right hemisphere in patients with ASD, which in this case might have interfered with the damage of the right amygdala. Gainotti (2012) proposed that the right amygdala is primarily responsible for automatic emotion processing.…”
Section: Discussionsupporting
confidence: 85%
“…It is therefore possible that the present findings may also be associated with social anxiety. A similar argument may be posed for other variables that have been found to be associated with paranoia and/or lateralisation, such as depression (e.g., Bourne & Vladeanu, in press;Kucharska-Pietura & David, 2003;Rabany, Weiser, Werbeloff, & Levkovitz, 2011) or theory of mind and autistic traits (e.g., Gooding & Pflum, 2011;Vladeanu, Monteith-Hodge, & Bourne, 2012). Indeed, it has been suggested that low self-esteem is a vulnerability factor for depression (Sowislo & Orth, 2012).…”
Section: Bourne and Mckaymentioning
confidence: 89%
“…Thus, the authors of this study hypothesized the existence of an interaction between ASD personality traits, emotion processing abilities, and the degree of brain hemisphere lateralization for processing emotions that are communicated through facial expressions. They noted that people with tendencies for social disinterest and rigidity may be likely to have stronger brain lateralization for emotion processing (Vladeanu et al, 2012).…”
Section: Differences In Brain Functionmentioning
confidence: 99%
“…The visual trials in the Vladeanu et al (2012) study included chimeric faces that displayed all of the basic emotions: anger, disgust, fear, happiness, sadness, and surprise. Analyses of results yielded no significant findings for female participants.…”
Section: Differences In Brain Functionmentioning
confidence: 99%